Study on Random Decrement Signature Under Different Triggering Level and Length of Time History - Wu, Jinzhi; Zheng, Xiujuan; Hu, Jie; Zhang, Yigang; Yuan, Fuh-Gwo (Topics in Modal Analysis & Testing, Volume 10, 2017)
Random Decrement Technique (RDT) is a widely used method to extract free decay response data by averaging time segments obtained under certain triggering condition from structural vibration response. And thus, different triggering condition will inevitably lead to different Random Decrement Signature (RDS) and different modal parameters. The quality of RDS has significant influence on the modal parameter identification results. Based on three assessments criteria for RDS's quality, statistical analysis of change law of RDS with different triggering level and length of time history are carried out by a SDOF system and a 6-DOF system. A multi-triggering method is proposed, by which a better RDS can be obtained. Numerical simulation and the practical engineering application verified the recommended method and values.